A recent change in the optical and γ-ray polarization of the Crab nebula and pulsar. Issue 3 (31st December 2015) - Moran, P.; Kyne, G.; Gouiffès, C.; Laurent, P.; Hallinan, G.; Redfern, R. M.; Shearer, A.
Abstract : We report on observations of the polarization of optical and γ-ray photons from the Crab nebula and pulsar system using the Galway Astronomical Stokes Polarimeter (GASP), the Hubble Space Telescope, Advanced Camera for Surveys and the International Gamma-Ray Astrophysics Laboratory satellite ( INTEGRAL ). These, when combined with other optical polarization observations, suggest that the polarized optical emission and γ-ray polarization changes in a similar manner. A change in the optical polarization angle has been observed by this work, from 109.5 ± 0 _.^° 7 in 2005 to 85.3 ± 1 _.^° 4 in 2012. On the other hand, the γ-ray polarization angle changed from 115 ± 11° in 2003–2007 to 80 ± 12° in 2012–2014. Strong flaring activities have been detected in the Crab nebula over the past few years by the high-energy γ-ray missions Agile and Fermi, and magnetic reconnection processes have been suggested to explain these observations. The change in the polarized optical and γ-ray emission of the Crab nebula/pulsar as observed, for the first time, by GASP and INTEGRAL may indicate that reconnection is possibly at work in the Crab nebula. We also report, for the first time, a non-zero measure of the optical circular polarization from the Crab pulsar+knot system.